AN INVESTIGATION OF TASKS DISTRIBUTED IN ENGLISH TEXTBOOK - Nisrina (PRASI, 2023)
The use of textbooks in the context of the EFL setting has come to the surge that teachers heavily relied on them in teaching-learning processes. This article investigated the organization of tasks distributed, in the textbooks, by identifying sequences of the task regarding task hierarchies based on Bloom's taxonomy and by exploring the total number of tasks distributed for each chapter in English textbook entitled When English Rings a Bell for the 7th grade of junior high school. The data were collected through content analysisThe findings of this study revealed that there was no systematic task distributed hierarchically based on Bloom’s Taxonomy and the total number of tasks distributed was randomly arranged through chapters. HOT’s level tasks did not exist in the tasks allocated. The findings of this study suggest that textbook developers must give more attention to the tasks allocated for each chapter regarding the rise of hierarchy and the distribution of total number.